Human Mesenchymal Stem Cell Therapy Reverses Su5416/Hypoxia-Induced Pulmonary Arterial Hypertension in Mice - Alencar, Allan K. N.; Pimentel-Coelho, Pedro M.; Montes, Guilherme C.; da Silva, Marina de M. C.; Mendes, Luiza V. P.; Montagnoli, Tadeu L.; Silva, Ananssa M. S.; Vasques, Juliana Ferreira; Rosado-de-Castro, Paulo Henrique; Gutfilen, Bianca; Cunha, Valéria do M. N.; Fraga, Aline G. M.; et al. (Frontiers in Pharmacology, 2018)
Abstract Aims: Pulmonary arterial hypertension (PAH) is a disease characterized by an increase in pulmonary vascular resistance and right ventricular (RV) failure. We aimed to determine the effects of human mesenchymal stem cell (hMSC) therapy in a SU5416/hypoxia (SuH) mice model of PAH. Methods and results: C57BL/6 mice (20-25 g) were exposure to a combination of hypoxia (4 weeks) and subcutaneous administration of the antagonist of vascular endothelial growth factor receptor (20 mg/kg SU5416, weekly; PAH mice). After 2 weeks of SuH exposure, PAH mice were randomly divided in groups either treated with vehicle (0.6 U/mL DNaseI in PBS) or 5 × 105 stem cells which were intravenously injected in the caudal vein of the animals. Ratio between pulmonary artery acceleration time and RV ejection time (PAAT/RVET), measure by echocardiography, was significantly reduced in the PAH mice, compared with controls, and therapy with hMSCs normalized this. Significant muscularization of the PA was observed in the PAH mice and hMSC reduced the number of fully muscularized vessels. RV free wall thickness was higher in PAH animals than in the controls, and a single injection of hMSCs reversed RV hypertrophy. Levels of markers of exacerbated apoptosis, tissue inflammation and damage, cell proliferation and oxidative stress were significantly greater in both lungs and RV tissues from PAH group, compared to controls. hMSC injection in PAH animals normalized the expression of these molecules which are involved with PAH and RV dysfunction development and the state of chronicity. Conclusion: These results indicate that hMSCs therapy represents a novel strategy for the treatment of PAH in the future.